Comparative Study of Torch Ginger Flower and Curry Leaves Tea: Physicochemical and Sensory Characteristics - Ramisham, Nur Sabrina; Seow, Eng Keng (Jurnal Pangan dan Agroindustri, 2026)
This study investigates the addition of torch ginger flowers and curry leaves to black tea to enhance its antioxidant properties. Physicochemical analysis revealed a decrease in pH due to organic acids, while the addition of these ingredients resulted in changes to a*, b*, and L* color values. Volatile compound analysis suggested potential anti-inflammatory and anticancer benefits. The formulations showed increased total phenolic and flavonoid content, higher antioxidant activity (ABTS, FRAP, DPPH), and increased tannin content, alongside a reduction in caffeine levels compared to the control. Sensory evaluation indicated no significant differences, confirming that the formulations preserved the black tea’s taste. These findings demonstrate that adding torch ginger flowers and curry leaves enhances the health benefits of black tea without altering its sensory qualities.